Does Procrastination Always Predict Lower Life Satisfaction? A Study on the Moderation Effect of Self-Regulation in China and the United Kingdom - Yang, Zeyang (Frontiers in Psychology, 2021)
Aims: Studies have shown the predictive effects of procrastination and self-regulation on well-being. However, little is known about the interactive effect between procrastination and self-regulation. This study explores whether self-regulation moderates the link between procrastination and well-being among British and Chinese young adults. Methods: This study adopted self-reported questionnaire survey among two hundred and sixty-five British and four hundred and seventy-five Chinese participants. SPSS and AMOS were used to test the moderation effect. Multi-group path analysis was used to compare the two countries. Results: Data analysis shows that self-regulation was a significant moderator of the relationship between procrastination and life satisfaction in China but not in the UK. Procrastination predicted low life satisfaction only among the Chinese students with low self-regulation. Discussion: This study indicates that the effects of procrastination on well-being could be changed at different levels of self-regulation. Cultural difference can be an important factor when investigating procrastination and its impacts.